A95 THE EFFICACY OF SURVEILLANCE COLONOSCOPY ON SURVIVAL IN INFLAMMATORY BOWEL DISEASE ASSOCIATED COLORECTAL CANCER: A SYSTEMATIC REVIEW & META-ANALYSIS. (1st March 2018) - Perera, S; Warner, A; Almotasen, R; Boldt, G; Matsuoka, H; Yan, B; Sey, M; Rahman, A; Palma, D A; Asfaha, S
Abstract: Background: Patients with inflammatory bowel disease (IBD) are at increased risk of developing colorectal cancer (CRC). This risk is related to disease extent, duration and severity. Current guidelines recommend routine colonoscopy 8–10 years after the initial onset of disease. However, no large controlled trials have investigated the efficacy of surveillance colonoscopy and the benefit remains unproven. Aims: A systematic review and meta-analysis was performed to evaluate whether surveillance colonoscopy for CRC impacts the survival of patients with IBD. Methods: A systematic review of MEDLINE and EMBASE databases was undertaken to identify studies that examined the impact of surveillance colonoscopy on overall survival of patients with IBD associated CRC. Three hundred and forty-five studies were screened by title and abstract, followed by a detailed review of twenty three studies. Only studies that included a control group of IBD patients (a surveillance versus a non-surveillance arm) were included in this analysis. Effect estimates (hazard ratios [HR]) and confidence intervals (CIs) were computed, with a fixed-effects model created to estimate the effects. Cochrane's Q and I 2 -statistics were used to assess study heterogeneity. Additionally Dukes stage of the tumour was compared between the surveillance and non-surveillance groups using the Fisher's exact test. Results: Four relevant studies were identified, and this included a total of 334 patients. Of these patients, 118 underwent surveillance colonoscopy, while 216 did not. Surveillance colonoscopy was associated with improved overall survival, with the HR of death being 0.354 in the surveillance group (95% CI 0.217–0.578; p<0.001). Furthermore, these studies were not found to be heterogeneous ( Q = 1.727, P = 0.631, I 2 = 0. 000). Analysis of pathology data from two of the studies demonstrated that in the surveillance group tumours were more likely to be diagnosed at an earlier stage (Dukes A, P < 0.001), than in the group that did not undergo surveillance where tumours were more likely to be diagnosed at a later stage (Dukes C and D, P = 0.018 and P = 0.017). Conclusions: Our systematic review and meta-analysis demonstrates that surveillance colonoscopy does in fact improve overall survival in patients with IBD and suggests that surveillance colonoscopy additionally provides the advantage of detecting earlier staged colorectal tumours than when no surveillance is performed. Funding Agencies: None